Alterações morfológicas na capsula do casco em potros Crioulos do nascimento ao desmame - de Souza, João Ricardo Malheiros; Pimentel, Anelise Maria Hammes; Folle, Vinícius Azevedo; Pfeifer, João Pedro Hübbe [UNESP]; Schuster, Aline Bacchieri Gallo; Segabinazzi, Lorenzo Garrido Teixeira Martini [UNESP]; Lau, Lucas Correa; Martins, Charles Ferreira (FapUNIFESP (SciELO), 2017)
South America has numerous Criollo horse breeding farms; however, information on foal hoof growth is still limited and identifying the ideal periods to apply corrective trimming is a frequent concern for horse owners. In the present study, a morphometric analysis of hoof growth was performed on 46 Criollo foals from birth to weaning (0-8 months). Results showed that hoof growth rate was higher in the first four months followed by a decrease until the eighth month. Average growth rate of the hoof was 0.21cm per month, whereas that of the heel was 0.14cm per month. However, no significant differences were observed between medial and lateral heel length or between limbs. Coronary band perimeter and solar width showed an average increase of 0.97cm and 0.46cm per month, respectively, and were significantly correlated (r=0.99, P≤0.01). The characteristic most positively correlated to biometric variables was foal age, followed by solar width, toe length, and coronary band perimeter. In conclusion, hoof length increase in Criollo foals was more intensive during the first four months of life.
Morphometric changes in the hoof capsule of criollo foals from birth to weaning
Keywords: Foals; Hoof capsule; Long-term study; Morphometric analysis